Stable Accumulation of Photosystem II Requires ONE-HELIX PROTEIN1 (OHP1) of the Light Harvesting-Like Family . Issue 3 (1st February 2018) - Myouga, Fumiyoshi; Takahashi, Kaori; Tanaka, Ryoichi; Nagata, Noriko; Kiss, Anett Z.; Funk, Christiane; Nomura, Yuko; Nakagami, Hirofumi; Jansson, Stefan; Shinozaki, Kazuo
Abstract : The OHP1 complex is indispensable for protein synthesis and the assembly machinery during de novo synthesis of PSII in plants. Abstract: The cellular functions of two Arabidopsis ( Arabidopsis thaliana ) one-helix proteins, OHP1 and OHP2 (also named LIGHT-HARVESTING-LIKE2 [LIL2] and LIL6, respectively, because they have sequence similarity to light-harvesting chlorophyll a / b -binding proteins), remain unclear. Tagged null mutants of OHP1 and OHP2 ( ohp1 and ohp2 ) showed stunted growth with pale-green leaves on agar plates, and these mutants were unable to grow on soil. Leaf chlorophyll fluorescence and the composition of thylakoid membrane proteins revealed that ohp1 deletion substantially affected photosystem II (PSII) core protein function and led to reduced levels of photosystem I core proteins; however, it did not affect LHC accumulation. Transgenic ohp1 plants rescued with OHP1-HA or OHP1-Myc proteins developed a normal phenotype. Using these tagged OHP1 proteins in transgenic plants, we localized OHP1 to thylakoid membranes, where it formed protein complexes with both OHP2 and High Chlorophyll Fluorescence244 (HCF244). We also found PSII core proteins D1/D2, HCF136, and HCF173 and a few other plant-specific proteins associated with the OHP1/OHP2-HCF244 complex, suggesting that these complexes are early intermediates in PSII assembly. OHP1 interacted directly with HCF244 in the complex. Therefore, OHP1 and HCF244 play important roles in the stable accumulation of PSII.